1995
DOI: 10.1139/v95-052
|View full text |Cite
|
Sign up to set email alerts
|

Solvent effects on the reactivity of solvated electrons with ions in tert-butanol/water mixtures

Abstract: Reactions of e; with the ions N H i V s , and H: showed different variations of rate with solvent composition in rerr-butanollwater mixtures from 0 to 100 mol% water. In pure rerr-butanol solvent at 298 K the respective values of k2 (lo6 m3 mol-I s-I) are 3.2, 13, and 42. The estimated value of reaction radius R, depends on the minimum number of solvent molecules needed between e; and the reactant ion to attain the static values of E of the bulk solvent used in the calculation of the Debye factor f ; R, is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 18 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…In support of them, our study of e; reactivity in tertbutanol (10) provides evidence that p, in tert-butanol is about (acid-base autodissociation) of alcohols produce a relatively high intrinsic conductivity, which means that relatively high 10 times higher than the mobility of a normal anion in this concentrations of e: must be used to obtain a sufficiently alcohol. The relevant data are presented below.…”
Section: Introduction a Normal Anion Or Alkoxide Ion These Measuremesupporting
confidence: 67%
See 2 more Smart Citations
“…In support of them, our study of e; reactivity in tertbutanol (10) provides evidence that p, in tert-butanol is about (acid-base autodissociation) of alcohols produce a relatively high intrinsic conductivity, which means that relatively high 10 times higher than the mobility of a normal anion in this concentrations of e: must be used to obtain a sufficiently alcohol. The relevant data are presented below.…”
Section: Introduction a Normal Anion Or Alkoxide Ion These Measuremesupporting
confidence: 67%
“…The purified alcohol contained 5 x lop4 mole fraction of equipment that is available at only two or three labs in the water (10). Up to 1 x mole fraction more water was world (1)(2)(3)(4)(5).…”
Section: Experimental and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of f estimated from Eq. (7) were calculated from fixed values of R r , namely, R r ½e À s þ ðNO 3 À Þ s ¼ 1:5 nm, and R r ½e À s þ ðNH 4 þ Þ s ¼ 1:0 nm [12]. The values of f for the reaction of e À s with (NO 3 À ) s are 0.6-0.8, and those for the reaction of e À s with (NH 4 + ) s are 2.5-3.3.…”
Section: Smoluchowski-debye Modelmentioning
confidence: 99%
“…All these studies showed that the reaction rate of e À s with solutes varied with solvent composition. Concerning, the reactivity tests of e À s with charged solutes in alcohol/water mixed solvents, there has been some more reports related with the transport properties of ions in solvent at different temperatures and compositions [11,12], where the reactivity of the solvated electrons is not only dependent on the properties of the solvent but also the nature of the coreactant. We have reported in previous article about the reactivity of solvated electrons with ammonium nitrate in 1-propanol/water mixed solvent system [13].…”
Section: Introductionmentioning
confidence: 99%